In vitro anti-inflammatory properties of Smilax campestris aqueous extract in human macrophages, and characterization of its flavonoid profile. (30th January 2020) - Salaverry, Luciana S.; Parrado, Andrea C.; Mangone, Franco M.; Dobrecky, Cecilia B.; Flor, Sabrina A.; Lombardo, Tomás; Sotelo, Agustina D.; Saccodossi, Natalia; Rugna, Ana Z.; Blanco, Guillermo; Canellada, Andrea; Rey-Roldán, Estela B.
Abstract: Ethnopharmacological relevance: Extracts of Smilax campestris Griseb (Smilacaceae) have been employed in the treatment of several inflammatory diseases as a traditional herbal medicine. However, the cellular and molecular mechanisms involved in the observed effects remain elusive. Macrophages are known to play a central role in inflammatory responses. These cells are activated in response to a diversity of danger signals and produce several mediators of inflammation that eventually regulate the immune response. For all the above mentioned, scientific evidence is required to support the popular use of S. campestris . Aim of the study: We aimed to investigate the anti-inflammatory effect of S. campestris aqueous extract (SME) in activated THP-1 human macrophages, on the production of some mediators of inflammation and oxidative stress in order to provide scientific support for its popular use. Materials and methods: The characterization of SME was assessed by HPLC-MS/MS. The production of the pro-inflammatory cytokines and chemokines was evaluated by ELISA. The activity of metalloproteases was evaluated by zymography. The subcellular localization of the NF-κB transcription factor was analysed by Western blot. The superoxide anion and glutathione levels were assessed by flow cytometry. The cytotoxicity induced by SME in THP-1 macrophages was also investigated by the LDH release test. Results: In the present study, we have identified catechin and glycosylated derivatives of quercetin (quercetin-3-O-glucoside, quercetin-3-O-galactoside, rutin and quercetin-3-rhamnoside) as major components of the aqueous SME. We found that SME significantly decreased the production of the pro-inflammatory cytokines tumour necrosis factor (TNF)- α, interleukin (IL)-1β, IL-6, IL-8 and monocyte chemoattractant protein (MCP)-1 and the activity of the metalloproteinase (MMP)-9, in lipopolysaccharide-activated macrophages derived from the monocytic cell line THP-1. Furthermore, SME diminished the expression of NF-κB p65 subunit in the nuclear fraction. In addition, SME decreased the production of superoxide anion in THP-1 macrophages, without altering the levels of reduced glutathione. Conclusion: These results suggest that SME exerts its anti-inflammatory effects in human activated macrophages by inhibiting the production of pro-inflammatory cytokines, matrix metalloproteinases and the NF-κB transcription factor pathway along with a reduction of oxidative stress mediators. Moreover, catechin and glycosylated derivatives of were identified by HPLC-MS/MS in SME. Our findings provide scientific support for the traditional use of the S. campestris extracts. Graphical abstract: Image 1